Stabilization of a DNA aptamer by ligand binding - Santos, Tiago; Lopes-Nunes, Jéssica; Alexandre, Daniela; Miranda, André; Figueiredo, Joana; Silva, Micael S; Mergny, Jean-Louis; Cruz, Carla (Biochimie, 2022)
G-rich aptamers such as AS1411 are small oligonucleotides that present several benefits comparatively to monoclonal antibodies, since they are easier to manufacture and store, have small size and do not stimulate an immune response. We analyzed AT11-B1, a modified sequence of AT11 (itself a modified version of AS1411), in which one thymine was removed from the bulge region. We studied G-quadruplex (G4) formation/stabilization using PhenDC3, PDS, BRACO-19, TMPyP4 and 360A ligands by different biophysical techniques, namely circular dichroism (CD), Förster resonance energy transfer (FRET-melting) and nuclear magnetic resonance (NMR). The CD spectra showed that AT11-B1 adopts a predominant G4 of parallel topology when the buffer contains KCl or when ligands are added. PhenDC3 induced a ΔTm of 30 °C or more of the G4 structure as shown by CD- and FRET-melting experiments. The ligands demonstrate high affinity for AT11-B1 G4 and the NMR studies revealed that the AT11-B1 G4 involves four G-tetrad layers. The in silico studies suggest that all ligands bind AT11-B1 G4, namely, by stacking interactions, with the possible exception of PDS that may bind to the loop/groove interface. In addition, molecular dynamics simulations revealed that nucleolin (NCL) interacts with the AT11-B1 G4 structure through the RNA binding domain (RBD) 2 and the 12-residue linker between RBD1,2. Moreover, AT11-B1 G4 was internalized into a NCL-positive tongue squamous cell carcinoma cell line. In a nutshell, this study may help the identification of the ligands scaffolds to bind and stabilize AT11-B1, improving the targeting towards NCL that is overexpressed in cancer cells.
Keywords: Ligands; G-kvadruplexy; spinocelulární karcinom; G-Quadruplexes; Humans; ligandy; Aptamers, Nucleotide; Carcinoma, Squamous Cell; aptamery nukleotidové; Tongue Neoplasms; lidé; nádory jazyka